Up-Regulation of the Biosynthesis and Release of Substance P through Wnt/β-Catenin Signaling Pathway in Rat Dorsal Root Ganglion Cells. - Yu-Sang Li; Yang Xi; Xiao-Jun Li; Chang-Long Leng; Mei-Mei Jia; Wei Kevin Zhang; He-Bin Tang (PLoS ONE, 2015)
To examine regulatory effects of β-catenin on the biosynthesis and release of substance P, a rat chronic constriction injury (CCI) model and a rat dorsal root ganglion (DRG) cell culture model were used in the present study. The CCI treatment significantly induced the overall expression of β-catenin (158 ± 6% of sham) in the ipsilateral L5 DRGs in comparison with the sham group (109 ± 4% of sham). The CCI-induced aberrant expression of β-catenin was significantly attenuated by oral administration of diclofenac (119 ± 6% of the sham value; 10 mg/kg). Importantly, aberrant nuclear accumulation of β-catenin in cultured DRG cells resulted in up-regulation of the PPT-A mRNA expression and the substance P release. The up-regulation of both the PPT-A mRNA expression and the substance P release by either a GSK-3β inhibitor TWS119 (10 μM) or a Wnt signaling agonist Wnt-3a (100 ng/ml) were significantly abolished by an inhibitor of cyclooxygenase-2 (COX-2; NS-398, 1 μM). Collectively, these data suggest that nociceptive input-activated β-catenin signaling plays an important role in regulating the biosynthesis and release of substance P, which may contribute to the inflammation responses related to chronic pain.